2020
DOI: 10.1186/s42358-020-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian Society of Rheumatology guidelines for axial spondyloarthritis – 2019

Abstract: Spondyloarthritis is a group of chronic inflammatory systemic diseases characterized by axial and/or peripheral joints inflammation, as well as extra-articular manifestations. The classification axial spondyloarthritis is adopted when the spine and/or the sacroiliac joints are predominantly involved. This version of recommendations replaces the previous guidelines published in May 2013. A systematic literature review was performed, and two hundred thirty-seven studies were selected and used to formulate 29 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 225 publications
0
22
0
4
Order By: Relevance
“…The most recently published guidelines for the management of axSpA recommended NSAIDs as the first line treatment, but none of them has addressed specifically the current role of NSAIDs in the treatment of patients with axSpA regarding efficacy, safety and therapeutic strategy [6,7,71]. The present systematic review and critical analysis of the available evidences have confirmed that NSAIDs are still the basis for the treatment of patients with axSpA, as they are effective in most part of those patients.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The most recently published guidelines for the management of axSpA recommended NSAIDs as the first line treatment, but none of them has addressed specifically the current role of NSAIDs in the treatment of patients with axSpA regarding efficacy, safety and therapeutic strategy [6,7,71]. The present systematic review and critical analysis of the available evidences have confirmed that NSAIDs are still the basis for the treatment of patients with axSpA, as they are effective in most part of those patients.…”
Section: Discussionmentioning
confidence: 68%
“…Based on the previous guidelines for the treatment of axSpA and the clinical experience, despite lack of evidence, the panel recommended a second NSAI D, regardless therapeutic class (selective COX-2 or not), could be used if the first one failed after 4 weeks. The total treatment period with NSAIDs should not exceed 12 weeks, if the predefined target is not achieved [6,7].…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with disease controlled with original anti-TNF or anti-IL-17, it is not recommended to change therapy with biosimilar products 31. This is related to the risk of differences in the therapeutic response of the original product with biosimilar products in terms of efficacy, safety, and tolerability in patients 32.…”
mentioning
confidence: 99%